The Practice of Overlapping Surgery Is Safe in Total Knee and Hip Arthroplasty. Issue 3 (25th September 2018) - Suarez, Juan C.; Al-Mansoori, Ahmed A.; Borroto, Wilfredo J.; Villa, Jesus M.; Patel, Preetesh D.
Abstract : Background: Overlapping surgery occurs when a surgeon performs 2 procedures in an overlapping time frame. This practice is commonplace in the setting of total joint arthroplasty and is intended to increase patient access to experienced surgeons, improve efficiency, and advance the surgical competence of surgeons and trainees. The practice of overlapping surgery has been questioned because of safety and ethical concerns. As the literature is scarce on this issue, we evaluated the unplanned hospital readmission and reoperation rates associated with overlapping and non-overlapping total joint arthroplasty procedures. Methods: We reviewed 3, 290 consecutive primary total knee and hip arthroplasty procedures that had been performed between November 2010 and July 2016 by 2 fellowship-trained senior surgeons at a single institution. Overlapping surgery was defined as the practice in which the attending surgeon performed a separate procedure in another room with an overlapping room time of at least 30 minutes. Patient baseline characteristics and 90-day rates of complications, readmissions, and reoperations were compared between overlapping and non-overlapping procedures. Subanalyses also were done on patients with a body mass index (BMI) of ≥30 kg/m 2 and those with an American Society of Anesthesiologists (ASA) score of 3 or 4. The level of significance was set at 0.05. Results: Of the 2, 833 procedures that met the inclusion criteria, 57% (1, 610) were overlapping and 43% (1, 223) were non-overlapping. Baseline demographics, BMI, and ASA scores were similar between the groups. No significant differences were found between the overlapping and non-overlapping procedures in terms of the 90-day rates of complications (5.2% vs. 6.6%, respectively; p = 0.104), unplanned readmissions (3.4% vs. 4.3%; p = 0.235), or reoperations (3.1 vs. 3.1; p = 1.0) in the analysis of the entire cohort or in subgroup analyses of obese patients and patients with an ASA score of 3 or 4. The total mean operating room time was 5.8 minutes higher for overlapping procedures. Conclusions: Overlapping procedures showed no increase in terms of the 90-day rates of complications, readmissions, or reoperations when compared with non-overlapping procedures. There was just over a 5-minute increase in mean operating room time for overlapping procedures. Our data suggest that overlapping surgery does not lead to detrimental outcomes following total knee arthroplasty or total hip arthroplasty. Future investigations evaluating patient-oriented outcomes and satisfaction are warranted. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.